Zygotes segregate entire parental genomes in distinct blastomere lineages causing cleavage-stage chimerism and mixoploidy - Destouni, Aspasia; Zamani Esteki, Masoud; Catteeuw, Maaike; Tšuiko, Olga; Dimitriadou, Eftychia; Smits, Katrien; Kurg, Ants; Salumets, Andres; Van Soom, Ann; Voet, Thierry; Vermeesch, Joris R.

(untitled) (Genome Research, 2016)
Dramatic genome dynamics, such as chromosome instability, contribute to the remarkable genomic heterogeneity among the blastomeres comprising a single embryo during human preimplantation development. This heterogeneity, when compatible with life, manifests as constitutional mosaicism, chimerism, and mixoploidy in live-born individuals. Chimerism and mixoploidy are defined by the presence of cell lineages with different parental genomes or different ploidy states in a single individual, respectively. Our knowledge of their mechanistic origin results from indirect observations, often when the cell lineages have been subject to rigorous selective pressure during development. Here, we applied haplarithmisis to infer the haplotypes and the copy number of parental genomes in 116 single blastomeres comprising entire preimplantation bovine embryos (n = 23) following in vitro fertilization. We not only demonstrate that chromosome instability is conserved between bovine and human cleavage embryos, but we also discovered that zygotes can spontaneously segregate entire parental genomes into different cell lineages during the first post-zygotic cleavage division. Parental genome segregation was not exclusively triggered by abnormal fertilizations leading to triploid zygotes, but also normally fertilized zygotes can spontaneously segregate entire parental genomes into different cell lineages during cleavage of the zygote. We coin the term “heterogoneic division” to indicate the events leading to noncanonical zygotic cytokinesis, segregating the parental genomes into distinct cell lineages. Persistence of those cell lines during development is a likely cause of chimerism and mixoploidy in mammals.